Improving Understanding of Compound Sentences Through Think Pair Share and Make a Match - Susanti, Romia Hari; Lasvenia, Anindyksa; Nurmawati, Lilik (Actual Insight, 2025)
This study aims to examine the effect of applying the Think Pair and Share learning model combined with the Make a Match educational media on improving students’ cognitive learning outcomes in multi-tiered compound sentence material in Grade V at Tanjungrejo 1 Public Elementary School. The research was motivated by the low achievement of students’ cognitive outcomes in understanding and constructing multi-layered sentences. The novelty of this study lies in the integration of the Think Pair and Share cooperative learning model with the Make a Match educational game in Indonesian language learning at the elementary school level. The research design employed classroom action research conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The intervention involved pair discussions through the Think Pair and Share model during the comprehension stage, followed by activities of matching parent and child sentence cards using the Make a Match method to reinforce understanding. Data were collected through observation, interviews, tests, and documentation. The findings revealed an increase in the completeness of cognitive learning outcomes from 71 percent in the first cycle to 82 percent in the second cycle. These results indicate that combining the Think Pair and Share model with the Make a Match media effectively enhances students’ learning engagement and cognitive abilities, and it is recommended as an alternative strategy for implementing cooperative and game-based learning in primary schools.